2017
DOI: 10.15171/jnp.2017.21
|View full text |Cite
|
Sign up to set email alerts
|

Chronic dietary oxalate nephropathy after intensive dietary weight loss regimen

Abstract: Background: Hyperoxaluria has been associated with nephrolithiasis as well as acute and chronic kidney disease. We present a case of end stage renal failure caused by excessive dietary oxalate intake in a dietary weight loss regimen. Case Presentation: A 51-year-old Caucasian male with the past medical history of type 2 diabetes mellitus, gout, hypertension and morbid obesity was referred to the primary care clinic after being found pale and easily fatigued. The patient had lost 36 kg over a 7-month period by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…At the same time, cryopyrin-null mice were immune to developing end-stage renal disease in response to high oxalate insult, showing that there is likely a significant genetic component to these cases of secondary oxalate nephropathy. More importantly, this and other similar studies have shown a mechanistic connection between oxalate nephropathy and crystal arthropathies such as gout, which may possibly be an underappreciated set of comorbidities, given that our patient and two other patients from similar case reports of secondary oxalate nephropathy all had gout [20][21][22][23][24].…”
Section: Discussionsupporting
confidence: 67%
“…At the same time, cryopyrin-null mice were immune to developing end-stage renal disease in response to high oxalate insult, showing that there is likely a significant genetic component to these cases of secondary oxalate nephropathy. More importantly, this and other similar studies have shown a mechanistic connection between oxalate nephropathy and crystal arthropathies such as gout, which may possibly be an underappreciated set of comorbidities, given that our patient and two other patients from similar case reports of secondary oxalate nephropathy all had gout [20][21][22][23][24].…”
Section: Discussionsupporting
confidence: 67%
“…Urinary oxalate is derived either exogenously from dietary oxalate intake and net intestinal absorption or endogenously from oxalate synthesis mainly in the liver ( 10 ). Most reported AON cases in the literature have attributed the cause to either high intakes of oxalate-containing foods or oxalate precursors ( 12 15 ) or malabsorption induced by short-bowel syndrome ( 16 ), including celiac disease ( 17 ), gastric surgery (Roux-en-Y gastric bypass) ( 18 ), inflammatory bowel disease ( 19 ), chronic pancreatitis or pancreatic insufficiency, etc. ( 20 , 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…Case reports have documented diet-induced ON secondary to spinach, kale, berries, nuts and nut milk, cocoa powder, wheat germ, green smoothies, chagas mushrooms and vitamin C supplements. [9][10][11][12][13][14] The majority followed this diet for presumed health benefits and had partial recovery with restriction of oxalate consumption, increased oral hydration and calcium acetate supplementation to bind gut oxalate.…”
Section: Discussionmentioning
confidence: 99%